STRATEGI BUMDES DALAM MENINGKATKAN PENDAPATAN ASLI DESA (STUDI PADA BUMDES SARI TANI, DESA RIMBO RECAP, KECAMATAN CURUP SELATAN, KABUPATEN REJANG LEBONG) - Yopisah; Fadli; Lisa M.N Puspita (JURNAL FAIRNESS, 2024)
The purpose of this study was to analyze the Sari Tani BUMDes strategy in increasing village original income in Rimbo Recap Village, south Curup District, Rejang Lebong Regency. The sample used in this study was Sari Tani BUMDes in Rimbo Recap Village, Curup Selatan District, Rejang Lebong Regency. This study uses Porter's five forces analysis test method. The results of this study indicate that the challenges faced by BUMDes Sari Tani are also the presence of newcomers. Where there will always be newcomers because similar business actors are doing the same business, people's purchasing power is currently still standard 50/50. This is caused by a lack of marketing in the business, the threat is the emergence of new business actors who become competitors. As for the solution taken by BUMDes Sari Tani through innovation in presenting interesting programs, the power of BUMDes Sari Tani's suppliers is not too influential. Because BUMDes Sari Tani is one of the central government programs so that the central government provides assistance through the regional government in supporting its business activities, BUMDes Sari Tani gets competitors from similar business actors, of course, because in the area around where BUMDes Sari Tani is located the business actor has a different regional topography. so that the business carried out is also the same and what can differentiate these businesses is the superiority of the commodities produced by the business actors themselves as well as innovations in the field of other services.